Lossless Data Deduplication: Alternatif Solusi untuk Mengatasi Duplicated Record - Handijono, Ardijan (Program Studi Teknik Informatika Universitas Pamulang, 2020)
The implications of poor data quality bring negative effects for organisation through: increased operational costs, inefficient decision-making processes, lower performance and decreased both employee and customer satisfaction. Generally duplicated records can be handled by elimination or merge, but when duplicated records are occur in master table and used in a transaction the handling becomes not easy. This paper seeks to provide data deduplication solutions without losing the historical value of the transaction. To save all duplicated records which related to the transactions we use mapping table between Dimension table and facs table. Using this approach the quality of Dimension table increased since for this handling duplicated records process include enrichment process and delete dirty records and all dupplicated records which related to the transactions can be access completely in data warehouse, no transaction data loss.